Biomarkers of idiosyncratic drug-induced liver injury (DILI) - a systematic review - Atallah, Edmond; Freixo, Cristiana; Álvarez-Álvarez, Ismael; Cubero, Francisco Javier; Gerbes, Alexander L; Kullak-Ublick, Gerd A; Aithal, Guruprasad P. (Taylor & Francis, 2021)
Introduction: Idiosyncratic drug-induced liver injury (DILI) is an unpredictable event, and there are no specific biomarkers that can distinguish DILI from alternative explanations or predict its clinical outcomes. Areas covered: This systematic review summarizes the available evidence for all biomarkers proposed to have a role in the diagnosis or prognosis of DILI. Following a comprehensive search, we included all types of studies in humans. We included DILI cases based on any threshold criteria but excluded intrinsic DILI, commonly caused by paracetamol overdose. We classified studies into diagnostic and prognostic categories and assessed their methodological quality. After reviewing the literature, 14 studies were eligible. Expert Opinion: Diagnostic studies were heterogeneous with regard to the study population and outcomes measured. Prognostic models were developed by integrating novel biomarkers, risk scores, and traditional biomarkers, which increased their prognostic ability to predict death or transplantation by 6 months. This systematic review highlights the case of need for non-genetic biomarkers that distinguish DILI from acute liver injury related to alternative etiology. Biomarkers with the potential to identify serious adverse outcomes from acute DILI should be validated in independent prospective cohorts with a substantial number of cases.
Keywords: Hígado -- Enfermedades; Medicamentos; DILI; Lesión hepática inducida por fármacos; Hepatotoxicidad